Religious Pluralism and National Identity in Contemporary Indonesia - Intan Anggraini; Nurul Hana; Hany Fawzy; Kgosi Mabena (Studies in Indonesian Contemporary Religiosity and Modern World, 2025)
Indonesia’s status as one of the most religiously diverse countries in the world presents unique challenges and opportunities for the formation of national identity. This paper explores how religious pluralism shapes Indonesia’s modern national identity, focusing on the tension between state-imposed unity and religious diversity. It critically examines the role of Pancasila, Indonesia’s state ideology, in fostering interfaith cooperation, and the ways in which religious communities navigate the complexities of modernity, politics, and social cohesion. Through an analysis of recent policy changes, interfaith dialogue initiatives, and grassroots movements, this paper contributes to the understanding of how religious pluralism impacts social harmony and national unity in Indonesia. The research highlights how various faith groups, including Islam, Christianity, Hinduism, and indigenous beliefs, engage with national discourse and politics, often attempting to balance religious expression with state-imposed secularism. The paper also discusses the rise of religious nationalism, exploring its implications for Indonesia's religious diversity and democratic values. This work contributes to the broader field of religious studies by addressing the intersection of religion, politics, and national identity in one of the world’s most complex multicultural societies.